2012
DOI: 10.1118/1.4738963
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of in‐field and out‐of‐field dose distributions from a linear accelerator operating with and without a flattening‐filter

Abstract: The build-up and depth-dose characteristics of a conventional "6 MV" beam can be maintained when changing to a flattening-filter-free modality by increasing the incident electron energy from 6.45 MeV to 8.0 MeV. This will at the same time reduce the out-of-field dose for regions up to 20 cm from the central axis by 10%-30% compared to the original FF situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 32 publications
5
28
0
Order By: Relevance
“…Data from FFF beams are represented as dashed lines while solid lines refer to standard flattened beams. As expected, 13,20 FFF beams presented lower peripheral dose relative to the flattened beams, with 10 MV FFF beams showing the lowest values.…”
Section: A Depth Doses Out Of the Fieldsupporting
confidence: 79%
See 1 more Smart Citation
“…Data from FFF beams are represented as dashed lines while solid lines refer to standard flattened beams. As expected, 13,20 FFF beams presented lower peripheral dose relative to the flattened beams, with 10 MV FFF beams showing the lowest values.…”
Section: A Depth Doses Out Of the Fieldsupporting
confidence: 79%
“…[10][11][12] These are the leakage through the linear accelerator head shielding; the head scatter (radiation scattered from the linac head, mainly from flattening filter and collimating system) in its two components of scattered photons and electron contamination; the internal (or patient) scatter (radiation scattered within patient or phantom). Studies on the out-of-field dose 10,[13][14][15] demonstrated that these components depend on beam quality, field size, and distance from the field edge. While the first two sources have been reduced by technological improvements, the internal scatter source cannot be physically avoided.…”
Section: Introductionmentioning
confidence: 99%
“…In‐field PDDs and profiles do not constitute validation of out‐of‐field accuracy; as such parameters depend overwhelmingly on the primary radiation beam, which does not guarantee that secondary components (head scatter and leakage) are adequately modeled. A further validation consideration is relevant near the phantom surface (at depths shallower than the beam's d max ), as the out‐of‐field dose near the surface is substantially elevated by electrons . Accuracy of calculated dose near the phantom surface should also be confirmed against measurements when relevant.…”
Section: Computational Approachesmentioning
confidence: 99%
“…Detailed Monte Carlo models (which include head shielding and structural components) have shown good agreement with measurements even beyond 50 cm from the field edge . Much simpler Monte Carlo models that include only beam‐line components have also been used . While simple models are capable of accounting for patient scatter outside the treatment field, they do not allow for proper modeling of head leakage and, potentially, collimator scatter.…”
Section: Computational Approachesmentioning
confidence: 99%
“…The mean photon energy of the beam thus decreases with the distance from the central axis. 41 However, the proportion of photons with an energy lower than 200 keV over a 3 cm diameter surface is only 2.6% in a 2 cm diameter field. This introduces a systematic error smaller than 0.5% on the determination of the dose integral.…”
Section: B Energy Dependencementioning
confidence: 99%